Composite ultrafiltration membranes with tunable properties based on a self‐assembling block copolymer/homopolymer system. Issue 21 (6th August 2015) - Vriezekolk, Erik J.; Kudernac, Tibor; de Vos, Wiebe M.; Nijmeijer, Kitty
ABSTRACT Composite ultrafiltration membranes were fabricated by coating a thin film of self‐assembling polystyrene‐block‐poly(ethylene oxide) (PS‐b‐PEO) block copolymers and poly(acrylic acid) homopolymers on top of a support membrane. Block copolymers self‐assembled into a nanostructure where the minority component forms cylinders, whereas homopolymers reside in the core of the cylinders. Selective removal of the homopolymers led to the formation of pores. The morphology of the polymer layer was controlled by varying the content of homopolymers or polymer concentration of the coating solution, which led to membranes with different molecular weight cutoffs (MWCOs) and permeabilities. Uniform pores were obtained using low homopolymer contents, whereas high homopolymer contents caused macrophase separation and resulted in large polydisperse pores or craters at the surface. The thickness of the block copolymer film also influenced the structure and performance of the membranes, where a thicker film results in a strong decrease in permeability but a lower MWCO. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2015, 53, 1546–1558